FORMATION OF AN INTEGRATED MANAGEMENT INFORMATION SYSTEM FORINNOVATION-ORIENTED ENTERPRISES ON THE BASIS OF MARKETING MANAGEMENT - STADNYK, Valentyna; YOKHNA, Vitaliy; NASKALNYI, Serhiy; CHELIY, Taras (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to establish scientific and methodological foundations for building an integrated system of information support for the management of production enterprises operating in markets with high dynamics of consumer needs and which must be innovation-oriented. The paper addresses the issue of increasing the efficiency and competitiveness of domestic industrial enterprises in conditions of high variability of consumer markets. Attention is drawn to the fact that the key factor for solving this problem is a management information support system relevant to the strategic development goals, which allows increasing the productivity of managerial work and the validity of decisions. The advantages and disadvantages of existing scientific and methodological approaches to information support for management activities (systemic, process, resource, innovation and socio-economic) and information technologies designed to support the adoption of management decisions in various functional areas of management are analysed and systematized. The importance of correlating the functional capabilities of the information support of the management system with the value of individual structural elements of business processes to maintain the overall competitiveness of the enterprise is emphasized. Given that in the conditions of high variability of modern consumer markets, such elements are innovation management, a model of information support for the activities of an innovation-oriented industrial enterprise has been developed The emphasis is on the leading role of the marketing function, which integrates key information blocks of functional subsystems into a single whole, thereby forming a common information space for making and implementing strategic decisions in terms of the strategic goals of the innovative development of the enterprise. The developed scientific and methodological approach corresponds to the principles of value-oriented management and is based on the advantages of the marketing function in working with arrays of information about the state of the market and requests of target consumer groups. It has a universal nature and practical significance for increasing the efficiency of the processes of digitalization of domestic business structures.